Research on the application of biomaterial-based responsive hydrogels in the tumor microenvironment - Wanrong Yue; Xiaoyu Zhu; Ming Wu; Wenyue Qiang; Yixin Yang; Ziyun Zhang; Youwei Wang; Yuanyin Teng; Mi Zhou (PeerJ)
The tumor microenvironment (TME) is a critical factor influencing the initiation, growth, and spread of solid tumors. Recent advancements highlight biomaterial-based responsive hydrogels as promising smart materials within the TME owing to their high biocompatibility, biodegradability, and sensitivity to various stimuli. This review details the fundamental properties, preparation techniques, and diverse applications of responsive hydrogels, specifically within the TME. Key applications include their use in targeted tumor therapy, controlled drug delivery, and modulation of the complex TME. Recent studies have shown how these hydrogels, by responding to environmental factors such as pH, temperature, or specific biomolecules, can enhance treatment efficacy while minimizing systemic toxicity. Additionally, challenges are identified in terms of hydrogel design, safety, and clinical translation, with future directions aimed at optimizing hydrogel interactions with tumor-specific conditions. This review provides a comprehensive assessment of the current landscape, shedding light on the potential and ongoing research in the field of hydrogel-mediated cancer therapy.